1997
DOI: 10.1111/j.1471-0528.1997.tb11547.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful methotrexate treatment of a viable pregnancy within a thin uterine scar

Abstract: Case reportA 37 year old woman presented in her fourth pregnancy eight weeks of gestation with recurrent episodes of vaginal bleeding for seven days. Her first delivery was by a lower segment transverse caesarean section at 33 weeks of gestation due to pre-eclampsia. Her second and third pregnancies ended by a normal vaginal delivery. On admission her pulse and blood pressure were normal. Pelvic examination revealed moderate bleeding from the cervical canal; the cervix was long and closed. The size of the uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 3 publications
2
95
0
3
Order By: Relevance
“…Debido a la baja frecuencia de este tipo de embarazo ectópico no existen guías universales de tratamiento y no existe consenso en cuanto al tratamiento de elección, en reportes de casos se ha utilizado manejo médico, como lo es el metotrexato, KCl y solución glucosada hiperosmolar, tanto a nivel sistémico como local (3,(15)(16)(17). En cuanto al manejo quirúrgico se ha visto que está contraindicado el legrado uterino debido a que el tejido trofoblástico se encuentra fuera de la cavidad uterina expuesta y puede llevar a potencial ruptura de la cicatriz uterina y disrupción miometrial con hemorragia severa (18).…”
Section: Discussionunclassified
“…Debido a la baja frecuencia de este tipo de embarazo ectópico no existen guías universales de tratamiento y no existe consenso en cuanto al tratamiento de elección, en reportes de casos se ha utilizado manejo médico, como lo es el metotrexato, KCl y solución glucosada hiperosmolar, tanto a nivel sistémico como local (3,(15)(16)(17). En cuanto al manejo quirúrgico se ha visto que está contraindicado el legrado uterino debido a que el tejido trofoblástico se encuentra fuera de la cavidad uterina expuesta y puede llevar a potencial ruptura de la cicatriz uterina y disrupción miometrial con hemorragia severa (18).…”
Section: Discussionunclassified
“…If the pregnant reported no clinical evidence of suffering, such us bleeding or abdominal pain, and the diagnosis is made at an early stage, we can consider a conservative management with systemic or local injection of methotrexate, potassium chloride, and hyperosmolar glucose [17,21,[27][28][29]. However, recent reports evidenced that the cases treated with local or systemic methotrexate, often required laparotomy due to massive hemorrhage [30].…”
Section: Discussionmentioning
confidence: 99%
“…Marked vaginal bleeding associated with scar pregnancy is frequently uncontrollable requiring hysterectomy (Herman et al 1995), although Valley et al (1998) reported that removal of trophoblastic tissue by hysterotomy was also complicated by massive bleeding. Conservative treatment of scar pregnancy with locally and/or systemically administered MTX has been reported recently (Lai et al 1995;Godin et al 1997;Ravhon et al 1997;Seow et al 2000). These conservative treatments avoid unnecessary laparotomy and preserve the patient's fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the severity of complications, it is important that early and accurate diagnosis of the disorder is obtained in order to preserve fertility. Recently, conservative treatment of scar pregnancy with locally and/or systemically administered methotrexate (MTX) has been reported (Lai et al 1995;Godin et al 1997;Ravhon et al 1997;Seow et al 2001). While these treatments avoid the need for unnecessary laparotomy, the control of profuse bleeding by conservative interventions has never been described precisely.…”
Section: © 2005 Tohoku University Medical Pressmentioning
confidence: 99%